Absolute rotation detection by Coriolis force measurement using optomechanics - Sankar Davuluri; Yong Li (New Journal of Physics, 2016)
In this article, we present an application of the optomechanical cavities for absolute rotation detection. Two optomechanical cavities, one in each arm, are placed in a Michelson interferometer. The interferometer is placed on a rotating table and is moved with a uniform velocity of $\dot{\bar{y}}$ with respect to the rotating table. The Coriolis force acting on the interferometer changes the length of the optomechanical cavity in one arm, while the length of the optomechanical cavity in the other arm is not changed. The phase shift corresponding to the change in the optomechanical cavity length is measured at the interferometer output to estimate the angular velocity of the absolute rotation. An analytic expression for the minimum detectable rotation rate corresponding to the standard quantum limit of measurable Coriolis force in the interferometer is derived. Squeezing technique is discussed to improve the rotation detection sensitivity by a factor of $\sqrt{{γ }_{m}/{ω }_{m}}$ at 0 K temperature, where ${γ }_{m}$ and ${ω }_{m}$ are the damping rate and angular frequency of the mechanical oscillator. The temperature dependence of the rotation detection sensitivity is studied.